Ambidexterity for Corporate Social Performance. Issue 2 (February 2016) - Hahn, Tobias; Pinkse, Jonatan; Preuss, Lutz; Figge, Frank
The literature on corporate social performance advocates that firms address social issues based on instrumental as well as moral rationales. While both rationales trigger initiatives to increase corporate social performance, these rest on fundamentally different and contradicting foundations. Building on the literature on organizational ambidexterity and paradox in management, we propose in this conceptual article that ambidexterity represents an important determinant of corporate social performance. We explain how firms achieve higher levels of corporate social performance through the ambidextrous ability to simultaneously pursue instrumentally and morally driven social initiatives. We distinguish between a balance dimension and a combined dimension of ambidexterity, which both enhance corporate social performance through distinct mechanisms. With the balance dimension, instrumental and moral initiatives compensate for each other – which increases the scope of corporate social performance. With the combined dimension, instrumental and moral initiatives supplement each other – which increases the scale of corporate social performance. The article identifies the most important determinants and moderators of the balance and the combined dimension to explain the conditions under which we expect firms to increase corporate social performance through ambidexterity. By focusing on the interplay and tensions between different types of social initiatives, an ambidextrous perspective contributes to a better understanding of corporate social performance. Regarding managerial practice, we highlight the role of structural and behavioral factors for achieving higher corporate social performance through the simultaneous pursuit of instrumental and moral initiatives.